Hartapu – Hittite afterlife following the empire - Banyai, Michael (ARAMAZD: Armenian Journal of Near Eastern Studies, 2024)
Historical, epigraphical, and linguistic reasons reinforce the view of TÜRKMEN–KARAHÖYÜK 1 (followingly: TKH 1) as a genuine 12th-century BC Hartapu inscription. There is visual evidence of its overwriting during the 8th century BC, made to conceal the identity of Muršili, the father of Hartapu, eliminating his royal titles, featuring otherwise in all other inscriptions of Hartapu. All the anachronistic features, diagnostic to the 8th century BC, identified by Goedegebuure et al. (2020), are limited to this part of the text. Hartapu’s texts can be stylistically integrated within a small group of Luvian inscriptions from the early 12th century BC. One can surmise his identity within the group of sons of Urḫi-Teššub, dealt with in CTH 569. This text, concerning the endowment of the sons of Muršili III, Urḫi-Teššub, under the reign of Tudḫaliya IV, allows the identification of the fief of Hartapu, adjacent to the one held at the same time by Kurunta, which he expanded after the fall of the Hittite empire. The revived 8th-century interest in the ancient inscription of Hartapu is best understood in context with the efforts of the Tuwati-Wasusarma dynasty to gain back some of Hartapu’s territory mentioned in TKH 1 lost on the other side of the Halys to the Phrygians since 850 BC. Archaeological evidence proves the presence of the Muški in Central Anatolia (Halys Bend) sometime before their first Assyrian attestation on the other side of the Taurus under Ninurta-apil-Ekur (1191–1179 BC). This corrects the general misapprehension, connecting the Muški with Gordion. The arrival of the Phrygians in Anatolia is associated with the radical cultural modifications at the end of phase YHSS 7B at Gordion, c. 900 BC, corresponding to the simultaneous desertion of European sites associated with the Bryges.